Measurement method of carbon dioxide using spatial decomposed parallel computing. (8th May 2019) - Liu, Nan; Jing, Weipeng; Song, Wenlong; Zhang, Jiawei
According to the carbon dioxide (CO2 ) characteristics of weak absorption in the ultraviolet and visible (UV-VIS) bands, a measurement method based on spatial decomposed parallel computing of traditional differential optical absorption spectroscopy is proposed to measure CO2 vertical column concentration in ambient atmosphere. Firstly, American Standard Profile is used to define solar absorption spectrum, and the spectrum acquisition of the incident light converged by the telescope is described as observed parameters. On these bases, spectrometer line model is established. Then, atmospheric radiation transmission is simulated using parallel computing, which obviously reduces the computational complexity while balancing the interference that participates in the fitting. Simulation analyses show that the proposed method can reduce the computational complexity, and run time is reduced by 1.18 s compared with IMLM and IMAP-DOAS in the same configuration. The proposed method can also increase accuracy, with its inversion error reduced by 5.3% and residual reduced by 0.8% than differential optical absorption spectroscopy. The spatial decomposed parallel computing method has advantages in processing CO2, and it can be further used in the research of carbon sink.